2023
DOI: 10.1155/2023/1293200
|View full text |Cite
|
Sign up to set email alerts
|

miR‐432‐5p Inhibits the Ferroptosis in Cardiomyocytes Induced by Hypoxia/Reoxygenation via Activating Nrf2/SLC7A11 Axis by Degrading Keap1

Wei Geng,
Shaohua Yan,
Xinyue Li
et al.

Abstract: Early reperfusion into the myocardium after ischemia causes myocardial ischemia–reperfusion (I/R) injury and ferroptosis was involved. Ischemia activates the expression of a series of oxidative stress genes and their downstream regulatory genes, including ferroptosis-related genes such as nuclear factor E2-related factor 2 (Nrf2), glutathione peroxidase 4 (GPX4), and SLC7A11. This study adopted primary cardiomyocytes and I/R in rats to evaluate the ferroptosis and changing of Nrf2-SLC7A11/heme oxygenase-1 (HO-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…It was reported elsewhere that the HO-1 inhibitor zinc protoporphyrin suppressed isoproterenol-induced myocardial ferroptosis [56]. It was found, in another study, that the cytoprotective and anti-ferroptotic effects of the MiR-432-5p mimic are associated with an increase in the HO-1 level in isolated cardiomyocytes subjected to H/R [57].…”
Section: The Role Of Kinases In the Regulation Of Ferroptosismentioning
confidence: 85%
See 4 more Smart Citations
“…It was reported elsewhere that the HO-1 inhibitor zinc protoporphyrin suppressed isoproterenol-induced myocardial ferroptosis [56]. It was found, in another study, that the cytoprotective and anti-ferroptotic effects of the MiR-432-5p mimic are associated with an increase in the HO-1 level in isolated cardiomyocytes subjected to H/R [57].…”
Section: The Role Of Kinases In the Regulation Of Ferroptosismentioning
confidence: 85%
“…In addition, the miR-432-5p mimic increased HO-1 expression in cardiomyocytes and decreased it in the Kelch-like ECH-associated protein 1 (Keap1) protein level. It was reported that Keap1 is an endogenous inhibitor of Nrf2 [57]. It was found that miR-432-5p-Lipo reduced infarct size by about 30% and inhibited ferroptosis in myocardial tissue in rats with CAO (30 min) and reperfusion (4 h) [57].…”
Section: The Role Of Non-coding Rna In the Regulation Of Ferroptosis ...mentioning
confidence: 99%
See 3 more Smart Citations